The Rise and Fall of National Bargaining in the Canadian Meat-Packing Industry - Forrest, Anne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
The author addresses the questions of why industry-wide bargaining was developed in the Canadian meat-packing industry and why it suddenly collapsed.